Transferência de calor e massa em materiais com forma complexa via método da análise concentrada. Estudo de caso: secagem de materiais cerâmicos - SILVA, Veralúcia Severina da (Instituto Federal do Amapá, 2021)
Drying is a thermodynamic process, in which there is simultaneous heat transfer and moisture removal of a porous material. Clay products exposed to drying without control may suffer cracks and deformations, reducing its quality post-drying. This work aims to study theoretical and experimental the drying of solids with complex shape. It was developed a mathematical model to describe heat and mass transfer during the drying process, using the global capacitance method of hollow bodies. The analytical solution of the governing equations was made using the variable separation method. It were realized experiments of chemical and thermo-hydric characterization of clay, and drying of hollow and non-conventional clay ceramic materials at different temperatures (60, 70, 80, 90 and 100ºC). Results of the chemical composition and granulometry, and mass loss and heating of ceramic parts are presented and analyzed. It was verified that the moisture loss process occurs at a lower velocity than the heating of the ceramic material, the temperature and body shape strongly affect heat and mass transport phenomena, drying at low temperature favors the reduction of the problems in the material post-drying and improvement in the final quality, and that Biot numbers of heat and mass transfer directly affect the time to the product to reach its equilibrium condition. Comparison between predicted and experimental moisture content and temperature permitted estimative of the convective heat and mass transfer coefficients at the surface of the material, with good precision.